The Effect of Diagenetic Evolution on Shale Gas Exploration and Development of the Longmaxi Formation Shale, Sichuan Basin, China - Wang, Jia; Tan, Xianfeng; Tian, Jingchun; Luo, Long; Gao, Xuanbo; Luo, Chao; Zeng, Chunlin; Zhang, Lei; Xue, Weiwei (Frontiers in Earth Science, 2021)
The diagenetic evolution is an important controlling factor of shale gas reservoir. In this study, based on field outcrop and drilling core data, analytical techniques including X-ray diffraction (XRD), field emission scanning electron microscope combined with a focused ion beam (FIB-FESEM), and energy dispersive spectroscopy (EDS) analysis were performed to determine diagenetic evolution of the Longmaxi Formation shale , and reveal effect of diagenetic evolution on the shale gas exploration and development in the Sichuan Basin, Southwest China. The diagenetic evolution can be divided into eodiagenesis, mesodiagenesis, and teleodiagenesis. The eodiagenesis and mesodiagenesis were subdivided into two and three evolution stages respectively both in Basin margin and center. Absorbed capacity and artificial fracturing effect of the Longmaxi Formation shale gas was related to mineral composition, which was influenced by the sediment characteristics and diagenetic evolution. Diagenetic system in the Basin margin was more open than that in Basin center due to different structural burial history. The more open diagenetic system consisting of more micro-fractures and soluble constitute (e.g. feldspar) was in favour for formation and preservation of secondary dissolved pores and organic pores in the Basin margin. The relatively closed diagenetic system with stronger compaction resulted in deformation of pore space in the central Basin due to different burial history and diagenetic evolution.